Long Range Wireless Point to Point Link Network on 5 GHz Frequency Band with VoIP - Rida KHAN; Rumsha ANSARI (International Journal of Applied Methods in Electronics and Computers, 2016)
802.11 Wi-Fi technology is commonly used for creating wireless access networks with a maximum range of one hundred meters. With careful planning and proper antennas, this same technology can also be used to make point to point links up to several kilometres. Since, it is not always feasible and wise to run cables over long distances to connect different networks, therefore, wireless links may turn out to be cost effective alternative to their counterpart wired links while creating long distance networks and providing network scalability. Wi-Fi-based point to point links can therefore be used to connect two local area network (LAN) segments, which besides being cost-effective, provides network scalability and other advantages such as high speed, centralized and easier management and high throughput for line of sight (LOS) applications. A Wi-Fi-based point to point link can extend the range of wireless LAN by a few hundred feet to few miles which can further be increased by using highly directional antennas for point to point links, while serving as a backup network in different organizations. So, we have designed a soft private branch exchange (PBX) system for a university campus or organization, facilitating voice over internet protocol (VoIP) calls and instant messaging, employing the idea of Wi-Fi- based point to point links. Moreover, we have also analysed the quality of service (QOS) of the given setup in terms of data rate and connectivity using bandwidth test and ping test respectively, for both transmission control protocol (TCP) and user datagram protocol (UDP) scenarios.